Cover Image. Issue 4 (19th July 2022) - Ou, Xumin; Yang, Zhishuang; Zhu, Dekang; Mao, Sai; Wang, Mingshu; Jia, Renyong; Chen, Shun; Liu, Mafeng; Yang, Qiao; Wu, Ying; Zhao, Xinxin; Zhang, Shaqiu; et al.
Abstract : Cover caption: The cover image is based on the Original Article Tracing genetic signatures of bat‐to‐human coronaviruses and early transmission of North American SARS‐CoV‐2 by Xumin Ou et al., https://doi.org/10.1111/tbed.14148 . Image Design by Xumin Ou & Zhishuang Yang. et al.